The Influence of Individual Differences in Sensitivity to Provocations on Provoked Aggression. Issue 3 (22nd February 2013) - Lawrence, Claire; Hutchinson, Laura
Abstract Using an adapted form of the Taylor Competitive reaction Time (TCRT) task [Taylor (1967). Journal of Personality, 35, 297–310], this study is the first to examine the influence of individual differences in sensitivity to provocations (SP) [Lawrence (2006). Aggressive Behavior, 32, 3, 241–252] as opposed to sensitivity to frustrations (SF) on provoked aggression (noise blasts delivered to a bogus partner). Participants (N = 144) played a competitive reaction time task against a bogus partner, who delivered increasingly loud noise blasts to participants on trials when the participant lost. The study also manipulated the partner's behavior such that, in initial trials, the partner either delivered moderate blasts to the participant or no blasts at all. While accounting for broad trait aggression, those high in SP delivered louder noise blasts to a bogus partner when provoked but not when unprovoked. These individuals also delivered more maximum blasts to the partner and delivered maximum blasts earlier in the TCRT. The effects of SP became non‐significant when the partner was initially non‐aggressive. Similarly, an initially non‐aggressive partner reduced participant aggression under later conditions of moderate provocation from the partner, but this effect became non‐significant under subsequent high provocation from the partner. While being related to SP, SF did not influence provoked aggression. Aggr. Behav. 39 :212‐221, 2013. © 2013 Wiley Periodicals, Inc.